Hazardous Properties of Molten Ammonium Dinitramide. Issue 10 (31st July 2020) - Comet, Marc; Schwartz, Cédric; Oudot, Franck; Schnell, Fabien; Spitzer, Denis
Abstract: The purpose of this article is to alert our peers on the danger faced by those who carry out experiments involving molten ammonium dinitramide (ADN). In recent experiments aiming at preparing submicron particles of this compound, a preliminary study of the sensitivity to impact of molten ADN was performed. These first tests have shown that the sensitivity threshold of molten ADN to impact is more than one order of magnitude lower that the one on solid ADN (<0.25 J vs. 4 J) and similar to the one of nitroglycerin (<0.25 J), making liquid ADN extremely hazardous to handle. Detonation tests, which were performed in strong steel sheaths open to one end, have shown that the initiation of the detonation and its subsequent propagation occur both in solid and liquid ADN charges, having a diameter of only 4 mm. The critical diameter of solid ADN which is between 25 and 40 mm according to literature, is therefore decreased by at least an order of magnitude when ADN is placed in strong metallic confinement. On the other hand, the detonation of liquid ADN produces stronger destructive effects than the detonation of solid ADN, meaning that the detonation mechanisms of this explosive are different in its two physical states. In conclusion, liquid ADN must be considered in practice as a more hazardous and powerful explosive than solid ADN. This raises the issue of all experiments in which ADN is likely to be formed in molten state. Abstract :